The Effectiveness of Using Gel Angelicca as Celebrity Endorser of ESQA Cosmetics to Indonesian Women on Instagram - Trisno Lidya Natania; Felicia Goenawan; Astri Yogatama (Petra Christian University, 2024)
ESQA Cosmetics is a cosmetic brand from Indonesia. ESQA Cosmetics is known as the first vegan cosmetics brand in Indonesia that uses Gel Angelicca as a celebrity endorser in its Marketing Public Relation (MPR) activities. This research was conducted to find out the effectiveness of a celebrity endorser, named Gel Angelicca, in promoting ESQA Cosmetics products to Indonesian women on Instagram. This research uses an online survey method which was distributed to 100 respondents using a Likert scale. The result of this research shows that Gel Angelicca as a celebrity endorser for ESQA Cosmetics has proven to be effective in delivering promotional messages to Indonesian women on Instagram by looking at the values in the TEARS model (Trustworthiness, Expertise, Attractiveness, Respect, Similarity). This research shows that the most effective TEARS model indicator in using Gel Angelicca as a celebrity endorser is the attractiveness indicator.